INDEKS KESESUAIAN WISATA TERUMBU KARANG DALAM PENGEMBANGAN PARIWISATA DI LAMPUNG SELATAN - Ahmad Herison; Yuda Romdania; Dipo Akbar; Doni Pramanda (Jurnal Pariwisata Pesona, 2020)
Abstract Indonesia has a vast coastal area and is very potential to be developed, one of which is in tourism. In the Lampung area itself, tourism activities are industries that are growing very rapidly. One of them is in South Lampung Regency, which is now starting to emerge new tourist attractions but still not well managed by the government or the local community. One of them is Sekepal Island which is a new tourist destination in South Lampung Regency. This destination is developed and managed independently by the local community. The purpose of this study was to analyze the suitability of coral reef ecotourism in the development of tourism in South Lampung Regency. This study uses the Tourism Completeness Index by Yulianda (2007). Data collection is done by observation, documentation. The scores obtained are then matched with assessment points so that the value of suitability from ecotourism can be obtained. The results of the study show that the coral reef suitability index, including the category, is quite suitable and can be developed in its potential. But in development also must involve the role of the community and the government to run perfectly. Based on the matter, the researchers suggested to the community, especially Totoharjo Village, to involve the Lampung Regency Tourism Office to develop coral reef ecosystems in the future. Then the suggestion for further research is that researchers are advised to conduct more in-depth research into all ecosystems in coastal areas, such as mangroves and coral reefs, and to involve more leaders in their fields in conducting future research.